Restoration of Normal Growth in Vegetatively Malformed “Kent” Mango (Mangifera indica L) Cultivar (University of Khartoum Journal of Agricultural Sciences, 2023)
The aim to restore normal growth in one year field grown treesof “Kent” mango cultivar suffering symptoms of vegetativemalformation. Single and combined foliar treatments of the growthregulators, BA, NAA, and GA3 were tested following a comprehensivetreatment composed of pruning malformed branches 5 cm below theinfected area, spraying with stroby (fungicide-acaricide), and fertilizationwith 100 g urea/ tree. Symptoms of malformation were not detected 6 and12 months after the treatment, even in control trees, suggesting theadequacy of the comprehensive treatment of spaying with stroby(fungicide – acaricide) and urea fertilization for the control of vegetativemalformation. However, single application of either GA3 or NAAenhanced growth significantly.